Fermi level-tuned optics of graphene for attocoulomb-scale quantification of electron transfer at single gold nanoparticles - Qing Xia (Nature Portfolio, 2019)
Measurement of single-molecule level electron transfer is restricted by detection limits in nanoampere to picoampere ranges. Here the authors develop graphene-based electrochemical microscopy to attain an attoampere-level detection limit for faraday current at single nanoparticles.